A New Scheme Based on Pixel-Intense Motion Block Algorithm for Residual Distributed Video Coding - Lijuan Sun; Zhaoxiao Lin; Fu Xiao; Jian Guo (International Journal of Distributed Sensor Networks)
Residual Distributed Video Coding (RDVC) is a branch of the Distributed Video Coding (DVC). By reducing the coding rate, the RDVC scheme gets a better rate-distortion performance. The overall performance of the traditional pixel-based RDVC scheme is better than the traditional transform-based domain DVC scheme. But the traditional RDVC scheme also has some application limitations; for example, the performance of RDVC is bad when it is applied to intense motion regions. And the pixel-based RDVC scheme cannot fully exploit the spatial correlations of the original information. In this paper, we propose a new approach of residual coding combined IMB (intense motion block) extraction algorithm with Low Density Parity Check (LDPC) and Baum-Welch iterative decoding algorithm. Experimental results show that the proposed scheme achieves better rate-distortion performance compared to traditional DVC and RDVC scheme.